Effects of soybean oil on rheological characteristics of dough under high hydrostatic pressure. Issue 5 (14th July 2022) - Jia, Shuqi; Cao, Jian; Dai, Yangyong; Cui, Bo; Yuan, Chao; Hou, Hanxue; Ding, Xiuzhen; Wang, Wentao; Zhang, Hui; Zhao, Luping
Abstract: In order to improve the stability of dough with soybean oil, this article explored the effect of soybean oil addition on the rheological characteristics of dough under high hydrostatic pressure. The results showed that, compared with the dough without soybean oil, the β‐sheet, disulfide bonds content, and gauche‐gauche‐gauche in the dough increased by 4.23%, 0.85 μmol/g, and 4.16%, respectively when the dough was added with 6% soybean oil, which improved the degree of cross‐linking polymerization of gluten protein and the stability of gluten network. Meanwhile, the dough had the highest elastic modulus and the lowest maximum creep compliance (6.85 × 10 −4 Pa −1 ), indicating that 6% soybean oil significantly increased the elasticity and hardness of the dough. The results of short‐range ordered structure and paste properties showed that with the addition of soybean oil, the ordered structure and paste viscosity decreased with the increase of soybean oil. Abstract : This experiment proved that the addition of 6% soybean oil was most conducive to the stability of DSO. The β‐sheet content and SS content in the dough improved the stability of the DSO, increasing the G ′ of the dough and reducing the J max .